TINGKAT POSITIVITAS PEMERIKSAAN KALIUM HIDROKSIDA PADA PASIEN OTOMIKOSIS - Widhi, Anriani Puspita Karunia Ning; Krisniawati, Nia; Darmawan, Anton Budhi; Nur Hestiyani, Rani Afifah (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Otomycosis is an opportunistic fungal infection of the external ear canal and is widespread worldwide. The clinical manifestations of otomycosis are non-specific symptoms such as earache, discharge, itching, hearing loss, feeling of fullness in the ear, and tinnitus. The most common etiology found is Aspergillus sp. and Candida sp. The purpose of this study was to assess the positivity level of KOH examination in patients with a clinical diagnosis of otomycosis. The method used in this research uses a descriptive quantitative approach. The research subjects were otomycosis patients at the ENT-KL clinic at Margono Soekarjo Hospital from April to August 2022. Samples were taken using Flexible minitip flocked sterile swabs (Copan, Italy) on white to black ear secretions. Swabs were isolated on Saboraud Dextrose Agar (SDA) mushroom culture media (Himedia, India) and for KOH examination. The results obtained in this study were 48(85.7%) positive KOH, positive culture and 8(14.3%) negative KOH, positive culture. In a sample of 56 patients with a clinical diagnosis of otomycosis the most common isolates were Aspergillus sp 32 (57.1%) and Candida sp (42.9%). KOH sensitivity and specificity test results for Aspergillus sp were 37.7% and 100%, while for Candida sp were 97.7% and 50%. The conclusion of this study is that the KOH examination has a positivity rate of 85.7%. This examination needs to be routinely carried out as an initial screening to support the clinical diagnosis of otomycosis.